The role of physiology in the development of golf performance - Smith, M. F. (Sports Medicine, 2010)
The attainment of consistent high performance in golf requires effective physical conditioning that is carefully designed and monitored in accordance with the on-course demands the player will encounter. Appreciating the role that physiology plays in the attainment of consistent performance, and how a player's physicality can inhibit performance progression, supports the notion that the application of physiology is fundamental for any player wishing to excel in golf. With cardiorespiratory, metabolic, hormonal, musculoskeletal and nutritional demands acting on the golfer within and between rounds, effective physical screening of a player will ensure physiological and anatomical deficiencies that may influence performance are highlighted. The application of appropriate golf-specific assessment methods will ensure that physical attributes that have a direct effect on golf performance can be measured reliably and accurately. With the physical development of golf performance being achieved through a process of conditioning with the purpose of inducing changes in structural and metabolic functions, training must focus on foundation whole-body fitness and golf-specific functional strength and flexibility activities. For long-term player improvement to be effective, comprehensive monitoring will ensure the player reaches an optimal physical state at predetermined times in the competitive season. Through continual assessment of a player's physical attributes, training effectiveness and suitability, and the associated adaptive responses, key physical factors that may impact most on performance success can be determined.